Analisis Perencanaan Kinerja dalam Perspektif Balanced Scorecard (Studi Kasus: Badan Standardisasi Nasional) - Prabowo, Testianto Hanung Fajar (Jurnal Ilmiah Administrasi Publik, 2020)
In the current era of openness, the performance results of government institutions in Indonesia are of high concern to the public. For this reason, Niven (2003) emphasizes that it is time to manage performance in government institutions that can always translate the vision into outcomes to improve performance results by using Balanced Scorecard (BSC). But the planning of the performance in the perspective of balanced scorecard in BSN is still inconsistent so that the performance results cannot be seen in an ongoing manner every year. This study aims to analyze performance planning in a BSC perspective at BSN based on the Nine to Steps Success Balanced Scorecard theory from Rohm (2003). In addition, this study also identifies the constraints and supporting factors that influence the planning. The result is known that the planning of the performance in BSC perspective at BSN does not go through the stages of strategic initiative and automatitation so that it affects the performance.